End-stage liver disease score and future liver remnant volume predict post-hepatectomy liver failure in hepatocellular carcinoma - Kong, Fan-Hua (World J Clin Cases, 2019)
BACKGROUND: Hepatocellular carcinoma (HCC) is the world’s sixth most common malignant tumor and the third cause of cancer death. Although great progress has been made in hepatectomy, it is still associated with a certain degree of risk of post-hepatectomy liver failure (PHLF), which extends the length of hospital stay and remains the leading cause of postoperative death. Studies have shown that assessment of hepatic functional reserve before hepatectomy is beneficial for reducing the incidence of PHLF. AIM: To assess the value of model for end-stage liver disease (MELD) score combined with standardized future liver remnant (sFLR) volume in predicting PHLF in patients undergoing hepatectomy for HCC. METHODS: This study was attended by 238 patients with HCC who underwent hepatectomy between January 2015 and January 2018. Discrimination of sFLR volume, MELD score, and sFLR/MELD ratio to predict PHLF was evaluated according to the area under the receiver operating characteristic curve. RESULTS: The patients were divided into two groups according to whether PHLF occurred after hepatectomy. The incidence of PHLF was 8.4% in our research. The incidence of PHLF increased with the decrease in sFLR volume and the increase in MELD score. Both sFLR volume and MELD score were considered independent predictive factors for PHLF. Moreover, the cut-off value of the sFLR/MELD score to predict PHLF was 0.078 (P < 0.001). This suggests that an sFLR/MELD ≥ 0.078 indicates a higher incidence of PHLF than an sFLR/MELD < 0.078. CONCLUSION: MELD combined with sFLR is a reliable and effective PHLF predictor, which is superior to MELD score or sFLR volume alone.